2016
DOI: 10.1001/jamapediatrics.2016.1936
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neurodevelopmental Outcomes and Neonatal Morbidities of Extremely Premature Infants With Differential Exposure to Antenatal Steroids

Abstract: IMPORTANCE Many premature infants are born without exposure to antenatal steroids (ANS) or with incomplete courses. This study evaluates the dose-dependent effect of ANS on rates of neonatal morbidities and early childhood neurodevelopmental outcomes of extremely premature infants. OBJECTIVE To compare rates of neonatal morbidities and 18-to 22-month neurodevelopmental outcomes of extremely premature infants exposed to no ANS or partial or complete courses of ANS. DESIGN, SETTING, AND PARTICIPANTS In this obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 28 publications
5
68
2
2
Order By: Relevance
“…Thus, the fetuses of the PE group were delivered in better condition than the controls. AST has been described as a preventive intervention for IVH, neonatal deaths, and neurodevelopmental impairment [15,16]. Although the majority of the mothers in both groups received AST prior to delivery, a high proportion of the PE mothers received AST in close proximity to delivery in our study.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, the fetuses of the PE group were delivered in better condition than the controls. AST has been described as a preventive intervention for IVH, neonatal deaths, and neurodevelopmental impairment [15,16]. Although the majority of the mothers in both groups received AST prior to delivery, a high proportion of the PE mothers received AST in close proximity to delivery in our study.…”
Section: Discussionmentioning
confidence: 60%
“…Antenatal corticosteroids have been used for accelerating lung maturity since the 1970s, and many randomized controlled trials have shown reduction in mortality, and other neonatal morbidities except BPD, which is not significantly affected [31]. This may be explained by increased survival of extremely preterm infants born after antenatal steroids exposure [32]. Though antenatal steroids are now standard of care for preterm infants, several questions including their effect on long-term outcomes in extremely preterm infants, ideal formulation, and dosing schedule remain to be answered.…”
Section: Strategies For Prevention Of Bpd: “Hit – or – Miss”mentioning
confidence: 99%
“…Our group recently noted differential benefits of ANS as a trichotomized variable (no/partial/complete course of ANS) on survival, neonatal morbidities, as well as neurodevelopmental outcomes at 18 to 22 months of age among extremely preterm infants, with maximum benefits noted for the complete ANS group. 28 The findings of the current study may have implications for the design of trials to evaluate outcomes of MPT infants, which should take into account the differential associations of neonatal morbidities with no, partial, and complete courses of ANS. Lower neonatal morbidities associated even with a partial course of ANS in this study support the prompt administration of ANS even in situations when likelihood of receiving a complete ANS course appears low due to insufficient time.…”
Section: Discussionmentioning
confidence: 89%